Beyond conventional sensing: Simultaneous synergy of artificial intelligence and nanomaterial enhanced electrochemical sensing for next generation monitoring of food quality and safety: A review - Muhammad Waseem; Muhammad Ammar Khan; Md Mehedi Hassan; Yilei Huang; Xiuqi Xia; Xiaomei Chen (Trends in Food Science & Technology, 2026)

Socioeconomic drivers and farmers’ perception of climate change impact on agroforestry adoption: a regression-based study in South Punjab, Pakistan - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee; Turkan Hasanova Allahverdi (Agroforestry Systems, 2026)

Engineering abiotic stress tolerance in cereal crops: current advances and future directions - Baber Ali; Abdul Rehman; Arafat Abdel Hamed Abdel Latef; Muhammad Imran; Muhammad Ammar Javed; Nathan Wise; Nijat Imin (Cereal Research Communications, 2026)

Revisiting iron nutrition: a nano–organic approach for enhanced wheat yield, antioxidant resilience, and photosynthetic pigments - Hafiz Muhammad Jhanzab; Farhat Yasmeen; Ayshah Aysh Alrashidi; Muhammad Tanveer Altaf; Riaz Ahmad; Mohamed Ebaid; Ammar AL-Farga (Cereal Research Communications, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Exploring the antimicrobial potential of plant-based bioactive compounds in meat products: advances in mechanistic insights, pathogen inhibition, and shelf-life extension - Farhang Hameed Awlqadr; Mohammed N. Saeed; Ammar B. Altemimi; Syamand Ahmed Qadir; Othman Abdulrahman Mohammed; Tablo H. Salih; Aryan Mahmood Faraj; Muhammad Waqar; Hassan Raza (Critical Reviews in Food Science and Nutrition, 2026)

Molecular detection of Toxoplasma gondii in Amblyomma gervaisi ticks infesting monitor lizards (Varanus bengalensis) - Muhammad Naeem; Muhammad Ammar Ameen; Hafiza Misbah Munir; Huma Fatima; Shakir Ullah; Hira Muqaddas; Kasim Sakran Abass; Adil Khan; Furhan Iqbal (Experimental and Applied Acarology, 2026)

Enhance soil phosphorus availability via the growth and decomposition of green manure crops in drylands - Gaohai Han; Rana Muhammad Ammar Asghar; Adnan Anwar Khan; Yupei Chen; Jiarong Wang; Shijie Wei; Chenxi Liu; Zhiqi Li; Zhaohui Wang; Donglin Huang; Xiaomin Wei; Weidong Cao; et al. (Soil and Tillage Research, 2026)

Examining the Role of Corporate Digital Orientation in Fostering Firms’ Green Innovation: Evidence from Chinese Firm Life Cycle Stages - Murtaza Hussain; Shaohua Yang; Umer Sahil Maqsood; Muhammad Waleed Younas; R. M. Ammar Zahid (Journal of Environmental Management, 2026)

Optimisation of biomass-derived Propanol–Gasoline blends for sustainable bioenergy utilisation using response surface methodology - Muhammad Arslan Aslam; Ammar Hashmi; Muhammad Ashfaq; Muneeb-ur Rehman; Shah Nawaz Khan; Fakhar-ul Hasnain; Cheol Woo Park (Biomass and Bioenergy, 2026)

YOLO-based real-time floating debris counting in urban rivers for flood monitoring and water resource management - Shaufikah Shukri; Latifah Munirah Kamarudin; Azfar Haniff Zuel Azwar; Noraini Azmi; Ammar Zakaria; Ahmad Shakaff Ali Yeon; Syed Muhammad Mamduh Syed Zakaria; Retnam Visvanathan (Environmental Monitoring and Assessment, 2026)
Urban flooding is increasingly exacerbated by the accumulation of floating debris in rivers, which obstructs water flow, degrades water quality, and poses significant risks to human safety and environmental sustainability. Effective monitoring of floating debris is therefore critical for early flood warning and long-term water resource management. This study presents a real-time monitoring framework that integrates deep learning-based object detection models, You Only Look Once (YOLO) with video surveillance for the identification and quantification of floating debris in urban rivers. Field deployments were conducted in flood-prone sites in Shah Alam, Malaysia, to evaluate the system under real-world environmental conditions. Results show that YOLOv7 achieved higher accuracy and robustness across diverse debris classes and lighting conditions compared to YOLOv9, with precision, recall, and F1-scores demonstrating strong detection reliability. Beyond technical accuracy, the system provides timely and actionable information for flood risk assessment, river management, and environmental monitoring. By automating debris detection and quantification, this study contributes to Sustainable Development Goals (SDGs) 11 (Sustainable Cities and Communities) and 13 (Climate Action), offering a scalable monitoring solution for flood-prone regions.

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

Allelopathic effects of rice husk on goosegrass (Eleusine indica) and lettuce (Lactuca sativa) - Nurul Solehah Binti Samsudin; Siti Aisyah Mohammad Taupik; Chia Poh-Wai; Dilipkumar Masilamany; Muhammad Ammar Yunus; Chuah Tse-Seng (South African Journal of Botany, 2026)

Orange peel derived biochar assisted rGO@MoS₂ composite for visible light driven ciprofloxacin degradation and hydrogen evolution - Asim Jilani; Mohsin Raza Dustgeer; Mohammad Omaish Ansari; Alishbah Zaka; Muhammad Adil Mansoor; Ammar A. Melaibari; Hussameldin Ibrahim (Journal of Water Process Engineering, 2025)

Techno-economic and environmental evaluation of hydrogen production from municipal solid waste via CaO-assisted gasification for biorefinery applications - Hafiz Muhammad Uzair Ayub; Muhammad Ammar; Muhammad Shahbaz; Tareq Al Ansari (Biomass and Bioenergy, 2025)

Cutting edge: ferroptosis in metabolic dysfunction-associated steatotic liver disease (MASLD) pathogenesis and therapy - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Muhammad Ikram Ullah; Subasini Uthirapathy; Subbulakshmi Ganesan; Abhayveer Singh; Anita Devi; Kamal Kant Joshi; Ahmed Salman Jasim; Abed J. Kadhim (Functional & Integrative Genomics, 2025)

P-solubilising bacteria and P-cycling genes drive soil P transformation during green manure decomposition - Adnan Anwar Khan; Yupei Chen; Rana Muhammad Ammar Asghar; Imran Azeem; Tahir Shah; Weidong Cao; Dabin Zhang; Yajun Gao (Agriculture, Ecosystems & Environment, 2025)

Climatic variability linkages with agroforestry adoption in Pakistan: a socio-ecological review - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee (Agroforestry Systems, 2025)

Remote sensing technologies for monitoring coral reef health under climate change - Ricky Anak Kemarau; Wee Hin Boo; Nurul Asyiqin Abu Bakar; Zulfaqar Sa'adi; Zaini Sakawi; Muhammad Ammar Fakhry Norzin; Wan Shafrina Wan Mohd Jaafar; Stanley Anak Suab; Oliver Valentine Eboy; Noorashikin Md Noor (Marine Environmental Research, 2025)

Mindsets matter: Reimagining the destination brand experience-environmental behaviour link through a cognitive lens - Muhammad I. Hossain; Arnold Japutra; Nurnobi Islam; Ammar Javed (Journal of Environmental Management, 2025)

Impact of COVID-19 on the prevalence of multi-drug-resistant bacteria: a literature review and meta-analysis - Haseeb Ahmed; Zain Ul Abideen; Ammar Azmat; Muhammad Irfan; Salman Anjum; Afaf Dirie (Antonie van Leeuwenhoek, 2025)

Ru-atom clusters embedded in Ti3C2Tx lattice for enhanced ammonium ion storage - Xiaofeng Zhang; Muhammad Sufyan Javed; Salamat Ali; Wei Xu; Peiao Lu; Awais Ahmad; Ammar M. Tighezza; Weihua Han; Kui-Qing Peng (Chemical Engineering Journal, 2025)

Carbon-negative process Integration: Techno-economic framework for biomass-blend bio-energy carbon capture and storage polygeneration with high-value co-product streams - Syed Muhammad Mustafa Rizvi; Bilal Kazmi; Syed Ali Ammar Taqvi; AbdulAziz AlGhamdi (Biomass and Bioenergy, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Beyond Data, Towards Sustainability: a Sydney Case Study On Urban Digital Twins - Ammar Sohail; Bojie Shen; Muhammad Aamir Cheema; Mohammed Eunus Ali; Anwaar Ulhaq; Muhammad Ali Babar; Asama Qureshi (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)
As urban areas grapple with unprecedented challenges stemming from population growth and climate change, the emergence of urban digital twins offers a promising solution. This paper presents a case study focusing on Sydney’s urban digital twin, a virtual replica integrating diverse real-time and historical data, including weather, crime, emissions, and traffic. Through visualization and data analysis techniques, the study explores some applications of this digital twin in urban sustainability, such as spatial ranking of suburbs and automatic identification of correlations between variables. Additionally, the research delves into predictive modeling, employing machine learning to forecast traffic crash risks using environmental data, showcasing the potential for proactive interventions. The contributions of this work lie in the comprehensive exploration of a city-scale digital twin for sustainable urban planning, offering a multifaceted approach to data-driven decision-making

Towards sustainable methanol production: energy, exergy, economics, and environmental evaluation of Thar coal gasification - Syeda Asra Arshad; Umna Nasir Ali; Syed Ali Ammar Taqvi; Bilal Kazmi; Ahsan Khalid; Muhammad Ahmer; Farooq Ahmad; Naveed Ahmad (Environment, Development and Sustainability, 2025)

Multiple integrated computational approach to analyse wound healing potential of Symplocos racemosa bark as Matrix metalloproteinase inhibitors - Hafiz Abdul Rafey; Adnan Amin; Samir Anis Ross; Mohamed El-Shazly; Muhammad Ammar Zahid; Shah Iram Niaz; Fakhar Ul Mahmood; Hammad Ullah (Natural Product Research, 2025)

Non-leguminous green manures improve labile phosphorus availability and crop yield in agroecosystems: A global meta-analysis - Adnan Anwar Khan; Imran Azeem; Jing Hui; Yupei Chen; Yuqi Yuan; Tahir Shah; Muhammad Adeel; Noman Shakoor; Rana Muhammad Ammar Asghar; Weidong Cao; Dabin Zhang; Yajun Gao (Soil and Tillage Research, 2025)

Mechanical and microstructural properties of sugarcane-polyethylene terephthalate fiber reinforced concrete - Fakhruddin; Muhammad Ammar Dzakir; Nurul Hudaya; Wilda Damayanti; Arwin Nurman; Sinta Renalia Rusli (Innovative Infrastructure Solutions, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Exploring multimetal interactions between FeNi3 alloy and Lu3Ga5O12 metal oxide for improved water splitting performance - Muhammad Ammar Hassan Shah; Zahoor Ahmad; Karam Jabbour; Khadija Bibi; Zubaida Fareed; Syed Imran Abbas Shah; Alanoud T. Alfagham; Abdallah M. Elgorban; Faryal Aftab; Muhammad Shuaib Khan (Fuel, 2025)

Advances in non-thermal technologies: A revolutionary approach to controlling microbial deterioration, enzymatic activity, and maintaining other quality parameters of fresh stone fruits and their processed products - Kashmala Chaudhary; Samran Khalid; Ammar B. Altemimi; Saqib Abrar; Sadia Ansar; Nabila Aslam; Mudassar Hussain; Rana Muhammad Aadil (Food Chemistry, 2025)

Developing Ag3VO4@ZnO electrode material for efficient oxygen evolution reaction showcasing its potential for sustainable energy applications - Ali Junaid; Faiqa Noreen; Abdus Sami; Karam Jabbour; Khadija Bibi; Muhammad Ammar Hassan Shah; Nigarish Bano; Muhammad Shuaib Khan; Asma A. Alothman; Syed Imran Abbas Shah (Fuel, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Sentry eyes? Women directors and corporate penalties - Muhammad Azeem Qureshi; Ammar Ali Gull; Tanveer Ahsan (Journal of Cleaner Production, 2024)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Triangular relation of food processing, nutrition, and osteoarthritis: A solution for the management and prevention of osteoarthritis? - Arashi Shahid; Ammar B. Altemimi; Iahtisham -Ul-Haq; Muhammad Inam-ur-Raheem; Roshina Rabail; Muhammad Hamdan Rashid; Sadia Kafeel; Muhammad Saad Akram; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Breeding for water-use efficiency in wheat: progress, challenges and prospects - Aqsa Hafeez; Shehzad Ali; Muhammad Ammar Javed; Rashid Iqbal; Muhammad Nauman Khan; Fatih ÇIĞ; Ayman EL Sabagh; Turki Abujamel; Steve Harakeh; Sezai Ercisli; Baber Ali (Molecular Biology Reports, 2024)

Oleuropein: Chemistry, extraction techniques and nutraceutical perspectives-An update - Anees Ahmed Khalil; Md. Mominur Rahman; Abdur Rauf; Md. Rezaul Islam; Sultana Juhara Manna; Ammar Ahmed Khan; Samee Ullah; Muhammad Nadeem Akhtar; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Role of nanofertilization in plant nutrition under abiotic stress conditions - Zhicong Dai; Zhiyun Huang; Die Hu; Misbah Naz; Muhammad Rahil Afzal; Muhammad Ammar Raza; Adalberto Benavides-Mendoza; Muhammad Tariq; Shanshan Qi; Daolin Du (Chemosphere, 2024)

Temporal characteristics of positive cloud-to-ground flashes from tropical thunderstorms - Muhammad Haziq Mohammad Sabri; Mohd Riduan Ahmad; Yuji Takayanagi; Shamsul Ammar Shamsul Baharin; Takeshi Morimoto; Zen-Ichiro Kawasaki; Mohd Zafri Baharuddin; Mohamad Zoinol Abidin Abd. Aziz; Mardina Abdullah; Vernon Cooray (Atmospheric Research, 2024)

Fault root cause analysis using degree of change and mean variable threshold limit in non-linear dynamic distillation column - Muhammad Shahid; Haslinda Zabiri; Syed Ali Ammar Taqvi; Mansoor Hai (Process Safety and Environmental Protection, 2024)

Integration of dual band radio waves and ensemble-based approach for rice moisture content determination and localisation - Noraini Azmi; Latifah Munirah Kamarudin; Ahmad Shakaff Ali Yeon; Ammar Zakaria; Syed Muhammad Mamduh Syed Zakaria; Hiromitsu Nishizaki; Latifah Mohamed; Xiaoyang Mao; Mohd Hafiz Fazalul Rahiman (Journal of Stored Products Research, 2024)

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

Observation of tropical positive cloud-to-ground flashes accompanied by chaotic and regular pulse trains - Muhammad Haziq Mohammad Sabri; Mohd Riduan Ahmad; Yuji Takayanagi; Muhammad Zuhair Bolqiah Edris; Shamsul Ammar Shamsul Baharin; Takeshi Morimoto; Zen-Ichiro Kawasaki; Mohd Zafri Baharuddin; Vernon Cooray (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Correction to: Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Improving the efficiency of photovoltaic-thermoelectric generator system using novel flying squirrel search optimization algorithm: Hybrid renewable and thermal energy system (RTES) for electricity generation - Muhammad Yaqoob Javed; Aamer Bilal Asghar; Khazina Naveed; Ali Nasir; Basem Alamri; Muhammad Aslam; Essam A. Al-Ammar; Zsolt Conka (Process Safety and Environmental Protection, 2024)

Trehalose-conjugated lentil-casein protein complexes prepared by structural interaction: Effects on water solubility and protein digestibility - Mohammad Alrosan; Ali Madi Almajwal; Ali Al-Qaisi; Sana Gammoh; Muhammad H. Alu'datt; Farah R. Al Qudsi; Thuan-Chew Tan; Ammar A. Razzak Mahmood; Khalid Bani-Melhem (Food Chemistry, 2024)

Calcium (Ca2+) signaling in plants: A plant stress perspective - Misbah Naz; Muhammad Rahil Afzal; Muhammad Ammar Raza; Saurabh Pandey; Shanshan Qi; Zhicong Dai; Daolin Du (South African Journal of Botany, 2024)

Very high frequency radiation emitted by negative narrow bipolar events occurred over malacca strait - Shamsul Ammar Shamsul Baharin; Mohd Riduan Ahmad; Muhammad Haziq Mohammad Sabri; Vernon Cooray (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Characterisation of the protein quality and composition of water kefir-fermented casein - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Stan Kubow; Ali Madi Almajwal; Sofyan Maghaydah; Ammar A. Razzak Mahmood; Ali Al-Qaisi; Haya AlFandi (Food Chemistry, 2024)

Tapping the nutraceutical potential of industrial hemp against arthritis and diabetes - A comprehensive review - Allah Rakha; Hina Rasheed; Ammar B. Altemimi; Sidra Tul-Muntaha; Iraj Fatima; Masood Sadiq Butt; Saddam Hussain; Zuhaib F. Bhat; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Recent advancement on water filtration membranes: Navigating biofouling challenges - Ammar Alnumani; Abdulrahman Abutaleb; Byungsung Park; Muhammad Mubashir (Environmental Research, 2024)

Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Pyridine-2,6-Dicarboxylic Acid As a Facile and Highly Selective “Turn-Off” Fluorimetric Chemosensor for Detection of Cu (II) Ions in Aqueous Media - Javed Hussain Shah; Shahzad Sharif; Muhammad Shahbaz; Bilal Riaz; Sundas Shahzad; Onur Şahin; Khurram Shahzad Munawar; Hijaz Ahmad; Essam A. Al-Ammar (Journal of Fluorescence, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Recent trends in hydrogen-associated treatments for maintaining the postharvest quality of fresh and fresh-cut fruits and vegetables: A review - Maratab Ali; Sara Batool; Nauman Khalid; Sajid Ali; Muhammad Ammar Raza; Xiaoan Li; Fujun Li; Zhang Xinhua (Food Control, 2024)

Do firms walk the talk when economic uncertainty is high? - Muhammad Azeem Qureshi; Ammar Ali Gull; Tanveer Ahsan; Muhammad Ansar Majeed (Journal of Cleaner Production, 2024)

Correction: Molecular characterization of bread quality contributing high and low‑molecular‑weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Molecular characterization of bread quality contributing high and low-molecular-weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

A bioactive chalcone from the aerial parts of Indigofera conferta Gillet - Maryam Isah; Salima Murtala; Sakynah Musa Abdullahi; Asmau Nasiru Hamza; Nasir Tajuddeen; Mu’ammar Lawal Dauda; Vuyisa Mzozoyana; Aliyu Muhammad Musa (Natural Product Research, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Plant breeding for harmony between sustainable agriculture, the environment, and global food security: an era of genomics‐assisted breeding - Aqsa Hafeez; Baber Ali; Muhammad Ammar Javed; Aroona Saleem; Mahreen Fatima; Amin Fathi; Muhammad Siddique Afridi; Veysel Aydin; Mükerrem Atalay Oral; Fathia A. Soudy (Planta, 2023)

Survey on actions and willingness towards the disposal, collection, and recycling of spent lithium-ion batteries in Malaysia - Gillvest Mathew; Wen Hui Teoh; Wan Muhammad Ammar Wan Abdul Rahman; Nurhidayah Abdullah (Journal of Cleaner Production, 2023)

Techno-economic assessment of sunflower husk pellets treated with waste glycerol for the Bio-Hydrogen production– A Simulation-based case study - Bilal Kazmi; Syed Ali Ammar Taqvi; Salman Raza Naqvi; Asif Ali Mirani; Muhammad Shahbaz; Muhammad Naqvi; Dagmar Juchelková; Gaber E. Eldesoky (Fuel, 2023)

Techno-economic sustainability assessment for bio-hydrogen production based on hybrid blend of biomass: A simulation study - Syed Muhammad Mustafa Rizvi; Bilal kazmi; Syed Ali Ammar Taqvi; Mahwish Mobeen Khan; Haslinda Zabiri; Danial Qadir; Ahmed Sayed M. Metwally (Fuel, 2023)

Investigation of control performance on an absorption/stripping system to remove CO2 achieving clean energy systems - Syed Ali Ammar Taqvi; Haslinda Zabiri; Salvinder Kaur Marik Singh; Lemma Dendena Tufa; Muhammad Naqvi (Fuel, 2023)

A systematic review on the bioremediation of metal contaminated soils using biochar and slag: current status and future outlook - Sajid Mehmood; Waqas Ahmed; Juha M. Alatalo; Mohsin Mahmood; Rana Muhammad Ammar Asghar; Muhammad Imtiaz; Naseer Ullah; Wei-dong Li; Allah Ditta (Environmental Monitoring and Assessment, 2023)

Co-opted directors and greenhouse gas emissions: Does ESG compensation matter? - Ammar Ali Gull; Aitzaz Ahsan Alias Sarang; Irfan Haider Shakri; Muhammad Atif (Journal of Cleaner Production, 2023)

Aspen plus simulation model of municipal solid waste gasification of metropolitan city for syngas production - Muzaffar Mehdi; Syed Ali Ammar Taqvi; Asif Ahmed Shaikh; Saad Khan; Salman Raza Naqvi; Muhammad Shahbaz; Dagmar Juchelková (Fuel, 2023)

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

A short review on the role of thyroxine in fast wound healing and tissue regeneration - Muhammad Fahad Amin; Muhammad Sarmad Zubair; Muhammad Ammar (Tissue and Cell, 2023)

Petrography and geochemistry of the Moulay Bouazza granitoids (Moroccan Variscan Central Massif). Implications for their origin and geodynamic setting - Ammar Oudy; Hassane Ouazzani; Muhammad Ouabid; Hicham El Messbahi; Mustapha Elabouyi; Afaf Amine; Hind El Haibi (Journal of African Earth Sciences, 2023)

Adsorption of Pb(II) from wastewater using a red mud modified rice-straw biochar: Influencing factors and reusability - Waqas Ahmed; Sajid Mehmood; Mohsin Mahmood; Sehrish Ali; Awais Shakoor; Avelino Núñez-Delgado; Rana Muhammad Ammar Asghar; Hongwei Zhao; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

Emissions and efficiency of an improved conventional liquefied petroleum gas cookstoves in Pakistan - Muhammad Usman; Muhammad Ammar; Muddassir Ali; Muhammad Zafar; Muhammad Zeeshan (Environment, Development and Sustainability, 2023)

Erratum to ‘Role of endophytic bacteria in salinity stress amelioration by physiological and molecular mechanisms of defense: A comprehensive review’ South African Journal of Botany, Volume 151, December 2022, Pages 33-46 - Baber Ali; Aqsa Hafeez; Muhammad Ammar Javed; Muhammad Siddique Afridi; Hina Ali Abbasi; Ayesha Qayyum; Tayyaba Batool; Abid Ullah; Romina Alina Marc; Soad K. Al Jaouni; Dalal Hussien M. Alkhalifah; Samy Selim (South African Journal of Botany, 2023)

Semi-supervised adaptive PLS soft-sensor with PCA-based drift correction method for online valuation of NOx emission in industrial water-tube boiler - Saidatul Hasniza Hasnen; Muhammad Shahid; H. Zabiri; Syed Ali Ammar Taqvi (Process Safety and Environmental Protection, 2023)

Microwave radiation associated with positive narrow bipolar events - Shamsul Ammar Shamsul Baharin; Mohd Riduan Ahmad; Muhammad Haziq Mohammad Sabri; Ammar Alammari; Ammar Ahmed Nasser Al-Kahtani; Gaopeng Lu; Zen Kawasaki; Vernon Cooray (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

Implications of the discovery of rapidly deposited lacustrine sediments in the Suwalong reach of the upper Jinsha River, SE Tibetan Plateau - Yongchao Li; Jianping Chen; Chun Tan; Feifan Gu; Yiwei Zhang; Muhammad Ammar; Qing Wang (Bulletin of Engineering Geology and the Environment, 2022)

Correction to: The nexus between corporate environment, social, and governance performance and cost of capital: evidence from top global tech leaders - Marina Nazir; Minhas Akbar; Ahsan Akbar; Petra Poulova; Ammar Hussain; Muhammad Azeem Qureshi (Environmental Science and Pollution Research, 2022)

Predicting Shale Volume from Seismic Traces Using Modified Random Vector Functional Link Based on Transient Search Optimization Model: A Case Study from Netherlands North Sea - Mohamed Abd Elaziz; Ashraf Ghoneimi; Ammar H. Elsheikh; Laith Abualigah; Ahmed Bakry; Muhammad Nabih (Natural Resources Research, 2022)

ATP-binding cassette transporters expression profiling revealed its role in the development and regulating stress response in Solanum tuberosum - Madiha Zaynab; Zongkang Wang; Athar Hussain; Khalida Bahadar; Mateen Sajid; Yasir Sharif; Muhammad Azam; Kalsoom Sughra; Muhammad Ammar Raza; Khalid Ali Khan; Shuangfei Li (Molecular Biology Reports, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Physiological impacts on construction workers under extremely hot and humid weather - Ammar Moohialdin; Bambang Trigunarsyah; Muhammad Saiful Islam; Mohsin K. Siddiqui (International Archives of Occupational and Environmental Health, 2022)

The nexus between corporate environment, social, and governance performance and cost of capital: evidence from top global tech leaders - Marina Nazir; Minhas Akbar; Ahsan Akbar; Petra Poulovo; Ammar Hussain; Muhammad Azeem Qureshi (Environmental Science and Pollution Research, 2022)

Hydrological evaluation of 14 satellite-based, gauge-based and reanalysis precipitation products in a data-scarce mountainous catchment - Naeem Saddique; Muhammad Muzammil; Istakhar Jahangir; Abid Sarwar; Ehtesham Ahmed; Rana Ammar Aslam; Christian Bernhofer (Hydrological Sciences Journal, 2022)

Genetic and expression deregulation of immunoregulatory genes in rheumatoid arthritis - Muhammad Zhaid Hussain; Ishrat Mahjabeen; Muhammad Shahid Khan; Naila Mumtaz; Syed Uzair Maqsood; Farooq Ikram; Syed Nazir Ahmed; Qurrat-ul-Ain Kalim; Rabia Abbas; Ahmed Ammar Cheema (Molecular Biology Reports, 2021)

Debris Flow Susceptibility Assessment and Runout Prediction: A Case Study in Shiyang Gully, Beijing, China - Yongchao Li; Jianping Chen; Yiwei Zhang; Shengyuan Song; Xudong Han; Muhammad Ammar (International Journal of Environmental Research, 2020)

Impact of interleukin IL-6 rs-1474347 and IL-10 rs-1800896 genetic polymorphisms on the susceptibility of HCV-infected Egyptian patients to hepatocellular carcinoma - Reham M. Abd El-Baky; Helal F. Hetta; Gopala Koneru; Marwa Ammar; Engy A. Shafik; Dina A Mohareb; Muhammad Abbas El-Masry; Haidi K. Ramadan; Mohamed Zakaria Abu Rahma; Michael A. Fawzy; Moustafa Fathy (Immunologic Research, 2020)

Dissecting microbial community structure in sewage treatment plant for pathogens’ detection using metagenomic sequencing technology - Abdulmoseen Segun Giwa; Nasir Ali; Muhammad Ammar Athar; Kaijun Wang (Archives of Microbiology, 2020)

Identification of archeological sites threatened with obliteration using space-borne and ground penetrating radars data in site of Tulul al-Ukhaidir, Iraq - Zaidoon Taha Abdulrazzaq; Jassim Muhammad Thabit; Ammar Jasim Al-Khafaji (Applied Geomatics, 2019)

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

The Small Matter of a Red Ox, a Particularly Sensitive Pink Cat, and the Quest for the Yellow Stone of Wisdom - Muhammad Jawad Nasim; Polina Denezhkin; Muhammad Sarfraz; Roman Leontiev; Yannik Ney; Ammar Kharma; Sharoon Griffin; Muhammad Irfan Masood; Claus Jacob (Current Pharmacology Reports, 2018)

Satellite-based rainfall estimation and discharge measurement of Middle Indus River, Pakistan - Syed Muhammad Zubair Younis; Muhammad Majid; Ahmad Ammar (Arabian Journal of Geosciences, 2017)

Multi-objective optimization model for water resource management: a case study for Riyadh, Saudi Arabia - Muhammad Al-Zahrani; Ammar Musa; Shakhawat Chowdhury (Environment, Development and Sustainability, 2016)

POM analyses of anti-kinase activity of thirteen peptide alkaloids extracted from Zizyphus species - Moulay H. Youssoufi; Taibi Ben Hadda; Ismail Warad; Muhammad Moazzam Naseer; Yahia Nasser Mabkhot; Ammar Bader (Medicinal Chemistry Research, 2015)

POM analyses of antimicrobial activity of some 2,3-armed 4,5,6,7-tetrahydro-1-benzothiophenes: favourable and unfavourable physico-chemical parameters in design of antibacterial and mycolytic agents - Taibi Ben Hadda; Sajal Srivastava; Barnali Das; Héctor Salgado-Zamora; Usama Shaheen; Ammar Bader; Muhammad Moazzam Naseer (Medicinal Chemistry Research, 2014)

Molecular Characterization of Chenopodium album Chloroplast Small Heat Shock Protein and Its Expression in Response to Different Abiotic Stresses - Noor Ul Haq; Muhammad Ammar; Asghari Bano; Dawn S. Luthe; Scott A. Heckathorn; Samina N. Shakeel (Plant Molecular Biology Reporter, 2013)